Systematic Literature Review (SLR) : Contextual Teaching Learning (CTL) Sebagai Upaya Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Lisdiana, Vinna; Isdaryanti, Barokah; Wijayati, Nanik; Avrilianda, Decky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a Systematic Literature Review (SLR) aimed at analyzing the effectiveness of the Contextual Teaching and Learning (CTL) approach in improving elementary school students' mathematics learning outcomes. The study was conducted on eighteen scientific articles published between 2022 and 2026 and obtained through manual searches in various accredited national journals. Articles were selected using the PRISMA guide based on established inclusion and exclusion criteria. The study results indicate that the application of CTL (Contextual Teaching and Learning) is consistently able to improve elementary school students' mathematics learning outcomes in various materials, ranging from fractions, plane figures, integers, to the volume of solid figures. Improvements in learning completeness occurred in each cycle in Classroom Action Research (CAR)-based research, while experimental studies showed significant differences between classes using CTL and control classes. CTL has proven effective because it connects mathematics material to students' real lives, making learning more meaningful, active, and enjoyable. Research gaps identified include a lack of cross-subject studies, a lack of experimental designs with control groups, and suboptimal technology integration in CTL implementation in elementary schools. These findings provide implications for teachers, researchers, and policymakers in developing more contextual and innovative mathematics learning strategies at the elementary school level.